STUDY OF THE IMMUNOLOGICAL MARKERS CD49d AND CD38 IN EARLY-STAGE B-CLL PATIENTS - Vanya Popova; Svetla Blazheva; Tsvetan Lukanov; Silvia Naneva; Nikolay Tzvetkov (Peytchinski Publishing, 2018)
Chronic lymphocytic leukemia (CLL) is characterized by the accumulation of B- lymphocytes into the blood stream, primary and secondary lymphoid organs as a consequence of defect in the apoptosis. Most frequently it affects people aged 67- 72. The greater part of CLL patients are in the early stage of the disease at the time of diagnosis, which gives a chance to delay the therapy. In 2008 the diagnostic criteria for CLL were revised. New prognostic and predictive factors were added in order to make the indications for starting the treatment more precise The aims of our study were: to determine the frequency of monoclonal B-cell lymphocytosis (MBL) in the subjects with absolute lymphocytosis, to establish a relationship between the flow cytometric markers CD49d and CD38 in patients with early stages Rai O-II / Binet A. To distinguish the patients with B- CLL from MBL as well as to define the expression of immunological markers we used flow cytometric analysis of peripheral blood. The results of our study have shown that a small number of patients met the criteria for MBL. Flow cytometric markers CD49d and CD38 associated with unfavorable prognosis were negative in most of the early stage patients.